2004
DOI: 10.1074/jbc.m403942200
|View full text |Cite
|
Sign up to set email alerts
|

UvsX Recombinase and Dda Helicase Rescue Stalled Bacteriophage T4 DNA Replication Forks in Vitro

Abstract: The rescue of stalled replication forks via a series of steps that include fork regression, template switching, and fork restoration often has been proposed as a major mechanism for accurately bypassing non-coding DNA lesions. Bacteriophage T4 encodes almost all of the proteins required for its own DNA replication, recombination, and repair. Both recombination and recombination repair in T4 rely on UvsX, a RecA-like recombinase. We show here that UvsX plus the T4-encoded helicase Dda suffice to rescue stalled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…More specifically, we wished to investigate whether there was evidence for E. coli possessing a transient template-switching mechanism of the kind first proposed by Higgins, Kato and Strauss in 1976 (6) for mammalian cells and later proposed for E. coli (4,5,16,19,24). In addition, a mechanism of this kind has been reconstructed in vitro, using purified phage T4 proteins (8,9). However, this model has been difficult to explore experimentally in vivo because the recombination event depends on informa-tional, rather than physical, exchange between DNA strands and because it occurs between identical sister strands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, we wished to investigate whether there was evidence for E. coli possessing a transient template-switching mechanism of the kind first proposed by Higgins, Kato and Strauss in 1976 (6) for mammalian cells and later proposed for E. coli (4,5,16,19,24). In addition, a mechanism of this kind has been reconstructed in vitro, using purified phage T4 proteins (8,9). However, this model has been difficult to explore experimentally in vivo because the recombination event depends on informa-tional, rather than physical, exchange between DNA strands and because it occurs between identical sister strands.…”
Section: Discussionmentioning
confidence: 99%
“…Because such transfer occurs between genetically identical sister duplexes, exchange cannot be detected by means of genetically marked strains. As a consequence, there is little in vivo evidence to support the occurrence of such a mechanism or to indicate its genetic requirements, such as dependence on RecA, though in vitro results with E. coli and phage T4 proteins strongly support such a model (5,7,8,9,16,17,(19)(20)(21). We have investigated the possible occurrence of such an alternative recombination mechanism for the completion of replication in the face of unrepaired DNA damage by transforming various E. coli strains with plasmids in which each strand carried, at specific staggered positions, a single thyminethymine pyrimidine (6-4) pyrimidinone [T-T (6-4)] lesion.…”
mentioning
confidence: 99%
“…Subsequent enzymological analyses using an eight-protein T4 DNA replication system in vitro showed that strand switching could indeed be promoted by DNA damage in the template strand and that the resulting replication repair was severely compromised when the mutant gp32 and gp41 proteins replaced their wild-type counterparts (Kadyrov and Drake 2003). Then, somewhat surprisingly, an alternative T4 system of replication repair was discovered in vitro in which gp32 and gp41 were replaced by the classical T4 recombinase UvsX and a different T4 DNA helicase, Dda (Kadyrov and Drake 2004). To date, these are the only genetically and enzymologically well-defined replication-repair systems.…”
mentioning
confidence: 99%
“…The translesion synthesis pathway is error prone due to the participation of low-fidelity DNA polymerases (21). The cleavage pathway is thought to be the dominant mode in bacteria, while replication repair (through template switching and translesion synthesis) is the dominant mode in T4 and eukaryotes (14).…”
mentioning
confidence: 99%